COMPONENT COMPOSITION OF ESSENTIAL OILS FROM LEAVES, INFLORESCENCES AND STEMS OF PEROVSKIA SCROPHULARIFOLIA GROWN IN UZBEKISTAN - Khudaiberdi Kurbandurdyevich Dzhumaev; Kirill Gavrilovich Tkachenko (Химия растительного сырья, 2023)
Essential oils as secondary metabolites, promising sources of biologically active substances with pronounced antimicrobial, antifungal and antiviral effects, are of considerable interest for study and possible use in medicine, pharmaceuticals, and aromatherapy. We have studied the composition of the essential oil of an endemic species for the first time Perovskia scrophularifolia Bunge. (Lamiaceae = Labiatae). This species of plant is of considerable interest as a medicinal plant, which is widely used in folk medicine in Uzbekistan and neighboring countries. Studies of biologically active substances of this species did not concern the essential oil. During the period of mass flowering in the inflorescences of Perovskia scrophularifolia contains 0.65%, in leaves – 0.71% of essential oil. The stems of the plant contain essential oils in small quantities. The composition and content of the components of the studied samples were determined according to the data of gas chromatographic and chromate-mass-spectrometric analysis. 26 substances were identified in essential oils from leaves, 43 from inflorescences and 18 substances from stems. The main components of essential oils from leaves and inflorescences are 1,8-Cineol up to 19.3% and Isobornyl acetate – up to 15.9%. This species is a promising source of biologically active compounds with biological activity (including antibiotic).